Effects of partial replacement of maize in the diet with crude glycerin and/or soyabean oil on ruminal fermentation and microbial population in Nellore steers - Granja-Salcedo, Yury Tatiana [UNESP]; Duarte Messana, Juliana [UNESP]; Carneiro De Souza, Vinícius [UNESP]; Lino Dias, Ana Veronica [UNESP]; Takeshi Kishi, Luciano [UNESP]; Rocha Rebelo, Lucas; Teresinha Berchielli, Telma [UNESP] (Cambridge University Press (CUP), 2017)
The objective of this study was to determine whether a combination of crude glycerin (CG) and soyabean oil (SO) could be used to partially replace maize in the diet of Nellore steers while maintaining optimum feed utilisation. Eight castrated Nellore steers fitted with ruminal and duodenal cannulas were used in a double 4×4 Latin square design balanced for residual effects, in a factorial arrangement (A×B), when factor A corresponded to the provision of SO, and factor B to the provision of CG. Steers feed SO and CG showed similar DM intake, DM, organic matter and neutral-detergent fibre digestibility to that of steers fed diets without oil and without glycerine (P>0·05). Both diets with CG additions reduced the acetate:propionate ratio and increased the proportion of iso-butyrate, butyrate, iso-valerate and valerate (P<0·05). Steers fed diets containing SO had less total N excretion (P<0·001) and showed greater retained N expressed as % N intake (P=0·022). SO and CG diet generated a greater ruminal abundance of Prevotella, Succinivibrio, Ruminococcus, Syntrophococcus and Succiniclasticum. Archaea abundance (P=0·002) and total ciliate protozoa were less in steers fed diets containing SO (P=0·011). CG associated with lipids could be an energy source, which is a useful strategy for the partial replacement of maize in cattle diets, could result in reduced total N excretion and ruminal methanogens without affecting intake and digestibility.
Keywords: Digestibility; Glycerol; Lipid supplementation; Protozoa; Rumen bacteria